2009
DOI: 10.1021/la902960a
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Carbon Nanotubes into a Lyotropic Liquid Crystal by Phase Separation in the Presence of a Hydrophilic Polymer

Abstract: Single-walled carbon nanotubes (SWNTs) were incorporated into a lyotropic liquid crystal (LLC) matrix formed by n-dodecyl octaoxyethene monoether (C(12)E(6)) at room temperature through spontaneous phase separation induced by nonionic hydrophilic polymer poly(ethylene glycol) (PEG). The quality of SWNTs/LLC composite was evaluated by polarized microscopy observations and small-angle X-ray scattering (SAXS) measurements. The results obtained clearly indicated that SWNTs have been successfully incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…4), the homogeneous dispersion became to precipitate. This unstability of G-dl can be ascribed to the desorption of 1 from the graphene lattice, which is reminiscent of the phenomenon observed in surfactant-wrapped CNTs [24,25]. In fact, the influence of temperature on the adsorption-desorption of 1 on the graphene surface can be already seen during the exfoliation of graphite.…”
Section: Thermo-responsive Propertiesmentioning
confidence: 90%
See 1 more Smart Citation
“…4), the homogeneous dispersion became to precipitate. This unstability of G-dl can be ascribed to the desorption of 1 from the graphene lattice, which is reminiscent of the phenomenon observed in surfactant-wrapped CNTs [24,25]. In fact, the influence of temperature on the adsorption-desorption of 1 on the graphene surface can be already seen during the exfoliation of graphite.…”
Section: Thermo-responsive Propertiesmentioning
confidence: 90%
“…Previously, we have reported that the dispersion state of surfactant-wrapped CNTs can be controlled by the variation of temperature [24,25]. Considering the structural similarity between graphene and CNTs, such rule might be also applied in graphene dispersions.…”
Section: Thermo-responsive Propertiesmentioning
confidence: 99%
“…The heating process may also induce the desorption of the amphiphilic molecules from the surface of the CNTs, leading to the aggregation of the CNTs [26]. To overcome these problems, Xin and coworkers developed a nondestructive strategy to incorporate SWNTs into LLCs utilizing the spontaneous phase separation between a nonionic surfactant (n-dodecyl hexaoxyethylene glycol monoether, C 12 E 6 ) and a hydrophilic polymer (poly(ethyiene glycol), (PEG)) [27]. After phase separation, an upper phase contains hexagonal LLCs incorporated by SWNTs together with a bottom isotropic phase consisting of PEG (Figure 1A and B).…”
Section: Carbon Nanotubes/llc Hybrid Materialsmentioning
confidence: 99%
“…For effective incorporation of SWCNTs into LLCs the method of phase separation in the presence of water soluble polymers was proposed [252][253][254]. The method consist of the initial incorporation of CNTs into the LLC phase formed by an anionic surfactant SDS or a cationic surfactant CTAB [252].…”
Section: Composite Polymers With Well Oriented Cntsmentioning
confidence: 99%
“…In the similar work the CNTs were initially incorporated in LLC formed by C 12 E 6 . Then the spontaneous phase separation was induced by addition of nonionic hydrophilic polymer PEG [253]. The hexagonal and lamellar phases were observed in dependence of the ratio of PEG to C 12 E 6 .…”
Section: Composite Polymers With Well Oriented Cntsmentioning
confidence: 99%